1989
DOI: 10.1073/pnas.86.13.5163
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of human immunodeficiency virus type 1 vpu.

Abstract: To investigate the role of vpu in the replication and cytopathicity of human immunodeficiency vrus type 1 (HIV-1), infectious proviruses were constructed that were isogenic except for the ability to produce the protein product of vpu. The vpu-encoded protein is shown to decrease the rate of syncytium formation and cell killing in infected CD4+ human T cells, to increase greatly the export of virus particles from infected cells, and to reduce the rate of accumulation of cell-associated viral proteins. The vpu p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
203
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(216 citation statements)
references
References 30 publications
12
203
0
1
Order By: Relevance
“…Bst-2 expression in A3.01 (lanes 3 and 4) and Jurkat cells (lanes 7 and 8) was near or below the limit of detection even after IFN␣ stimulation. This result is surprising because both A3.01 and Jurkat T cell lines were found to require Vpu for efficient virus release (1,10). FACS analyses confirmed the absence of cell surface Bst-2 in Jurkat cells whereas H9 cells were positive for surface Bst-2 (Fig.…”
Section: Hiv-1 Vpu Enhances the Release Of Virions From Infected Cellsmentioning
confidence: 75%
See 1 more Smart Citation
“…Bst-2 expression in A3.01 (lanes 3 and 4) and Jurkat cells (lanes 7 and 8) was near or below the limit of detection even after IFN␣ stimulation. This result is surprising because both A3.01 and Jurkat T cell lines were found to require Vpu for efficient virus release (1,10). FACS analyses confirmed the absence of cell surface Bst-2 in Jurkat cells whereas H9 cells were positive for surface Bst-2 (Fig.…”
Section: Hiv-1 Vpu Enhances the Release Of Virions From Infected Cellsmentioning
confidence: 75%
“…CD317 ͉ host restriction ͉ tetherin ͉ virus assembly V pu is an 81-aa type 1 integral membrane protein (1, 2) that has been shown to cause proteasomal degradation of CD4 (3,4), enhance the release of virions from infected cells (5), and prevent endocytosis of nascent viral particles (6)(7)(8)(9)(10)(11). These latter biological activities of Vpu are mechanistically distinct from CD4 degradation and involve different structural domains in Vpu.…”
Section: Hiv-1 Vpu Enhances the Release Of Virions From Infected Cellsmentioning
confidence: 99%
“…If rates of CTL-dependent killing are much faster in SIV infections, then it would suggest that rates of CTLindependent killing must be slower. Although there are some in vitro data that are consistent with this hypothesis showing that both activation-induced cell death (40) and viral cytotoxicity (41,42) may be reduced in SIV infection, it remains a hypothesis to be tested in studies that evaluate the in vivo CTL-independent death rate of productively infected cells in humans and nonhuman primate models.…”
Section: Discussionmentioning
confidence: 85%
“…HIV‐1 Viral protein U (Vpu) 59, 60 is renowned for its role in proteasomal degradation of CD4 61, 62 and enhancement of HIV‐1 release from infected cells 63, 64, 65 in a cell type‐dependent manner 66. In 2008, two independent laboratories showed that cell type‐specific expression of BST‐2 correlates with Vpu‐dependent release of HIV‐1.…”
Section: Viral Antagonists Of Bst‐2 and Neutralization Of Bst‐2 Antivmentioning
confidence: 99%